The Generation and Regulation of Tissue-Resident Tregs and Their Role in Autoimmune Diseases - Shuang Wang; Xueyang Zou; Yi Zhang; Xiaoya Wang; Wei Yang; Yi Li (Journal of Immunology Research)
Regulatory T cells (Tregs), as an important subset of T cells, play an important role in maintaining body homeostasis by regulating immune responses and preventing autoimmune diseases. In-depth research finds that Tregs have strong instability and plasticity, and according to their developmental origin, Tregs can be classified into thymic-derived Tregs (tTregs), endogenous-induced Tregs (pTregs), which are produced by antigen-stimulated T cells in the periphery in vivo, and induced Tregs (iTregs), which differentiate from naïve T cells in vitro. In recent years, studies have found that Tregs are divided into lymphatic and tissue-resident Tregs according to their location. Research on the generation and function of lymphoid Tregs has been more comprehensive and thorough, but the role of tissue Tregs is still in the exploratory stage, and it has become a research hot spot. In this review, we discuss the instability and plasticity of Tregs and the latest developments of tissue-resident Tregs in the field of biology, including adipose tissue, colon, skeletal muscle, and other Tregs that have been recently discovered as well as their production, regulation, and function in specific tissues and their role in the pathogenesis of autoimmune diseases.